THREE-DIMENSIONAL DC RESISTIVITY FORWARD MODELLING USING FINITE ELEMENTS IN COMPARISON WITH FINITE-DIFFERENCE SOLUTIONS - Li Yu.; Spitzer K. (My University, 2002)
A 3-D finite-element scheme for direct current resistivity modelling is presented. The singularity is removed by formulating the problem in terms of the secondary potential, which improves the accuracy considerably. The resulting system of linear equations is solved using the conjugate gradient method. The incomplete Cholesky preconditioner with a scaled matrix has been proved to be faster than the symmetric successive overrelaxation preconditioner. A compact storage scheme fully utilizes the sparsity and symmetry of the system matrix. The finite-element (FE) and a previously developed finite-difference (FD) scheme are compared in detail. Generally, both schemes show good agreement, the relative error in apparent resistivity for a vertical dike model presented in this paper is less than 0.5 per cent overall. The FD scheme produces larger errors near the conductivity contrast, whereas the FE scheme requires approximately 3.4 times as much storage as the FD scheme and is less robust with respect to coarse grids. As an improvement to the forward modelling scheme, a modified singularity removal technique is presented. A horizontally layered earth or a vertical contact is regarded as the normal structure, the solution of which is the primary potential. The effect of this technique is demonstrated by two examples: a cube in two-layered earth and a cube near a vertical contact.
Keywords: 3-D RESISTIVITY MODELLING; DC GEOELECTRICS; FINITE DIFFERENCES; FINITE ELEMENTS; PRECONDITIONING; SINGULARITY REMOVAL